Involvement of Substance P and the Neurokinin-1 Receptor in Radiation-Induced Hair Loss in Mice - Kouichi Yamamoto; Naoko Kureyama; Keiko Asano; Toshiji Ikeda; Atsushi Yamatodani (Elsevier, 2010)
We investigated the involvement of substance P (SP) and the neurokinin-1 receptor (NK1 R) in the development of radiation-induced hair loss in mice. A dose of 40 Gy of gamma irradiation induced hair loss from the 10th to at least the 60th day after irradiation. A specific NK1R antagonist, CP-99,994, significantly delayed radiation-induced hair loss and reduced its severity. Furthermore, gamma irradiation induced the expression of preprotachykinin-A, a precursor protein of SP, mRNA in irradiated murine skin on the 10th and 30th days after irradiation. These results indicated that gamma irradiation-induced hair loss was mediated by SP via NK1R. Keywords:: radiation-induced hair loss, substance P, neurokinin-1 receptor